Artifacts & Opportunity: Science and Technology Collections in Canada - Fisher, Victoria; Weidenhammer, Erich (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2024)
Across Canada, dozens of small artifact collections—whether hosted by national museums, smaller institutions, or simply stored in a university hallway cupboard—form an important yet largely untapped record of Canadian history. Assembled from laboratories, hospitals, homes, factories, farms, and fieldwork, such collections allow us to explore aspects of Canadian scientific and technological practice, innovation and labor that may be inaccessible through texts alone.